Steel corrosion-induced concrete cracking - Zhao, Yuxi; Jin, Weiliang (Butterworth-Heinemann is an imprint of Elsevier, 2016)
Annotation 'Steel Corrosion Induced Concrete Cracking' presents the latest advances in the origin, mechanism and development of corrosion-induced cracking in concrete. It investigates topics including expansion coefficient and elastic modulus of steel corrosion, rust layer and rust distribution, spatial distribution of corrosion products, and the shape of corrosion-induced cracks.
5.2.1 Reinforced Concrete Specimens.
Keywords: Concrete -- Testing.; Reinforcing bars -- Corrosion.; Concrete -- Corrosion.; Concrete -- Deterioration.; Concrete -- Cracking.; Concrete -- Fracture.; elektronické knihy; electronic books